Peralihan Penetapan Hak Asuh Anak di Bawah Umur Dalam Perkara Penguasaan Anak ( Studi Putusan Nomor 685/Pdt.G/2022/PA.Lahat.) - Ramadon, Ahmad; Yahya, Taufik; Muhamad Daud Abdul Kadir, Sulhi (Universitas Jambi, Fakultas Hukum, 2026)
The purpose of this study is to examine the legal provisions concerning the custody of minor children in Indonesia and to analyze the basis for determining the custody of minor children in child possession cases in Decision Number 685/Pdt.G/2022/PA.Lahat. The problem of this research is how the legal regulation regarding the custody of minor children in Indonesia is arranged and what is the basis for determining the custody of minor children in child possession cases based on Decision Number 685/Pdt.G/2022/PA.Lahat. The research method is normative juridical. The results of the study explain that the legal regulation regarding the custody of minor children can be found in Law Number 1 of 1974 concerning Marriage, Law Number 23 of 2002 concerning Child Protection, and the Compilation of Islamic Law (KHI). As for the basis for determining the custody of minor children, which was originally granted to the mother, the court, based on the judge’s legal considerations and trial facts, decided to grant custody to the father because the mother was deemed unfit for caregiving. The minor child in the case was proven not to be directly cared for by the mother but was instead cared for by a third party, namely the grandmother.